Cat: The importance of a correct management and basic anaesthetic monitoring in a tension pneumothorax and tracheal foreign body. Issue 1 (24th August 2016) - Cerasoli, Ilaria; Polis, Ingeborgh; Schauvliege, Stijn; Van der Vekens, Elke; Bosmans, Tim
Abstract : A six‐year‐old, male neutered, European domestic shorthair cat was presented at the emergency service of the Ghent University Small Animal Clinic with severe respiratory distress, subcutaneous emphysema and suspicion of an oesophageal foreign body reported by the referring veterinarian. After a radiographic study, a clinical examination suggested the presence of pneumothorax. Emergency thoracocentesis and thoracotomy were performed. Monitoring consisted of electrocardiography, capnography, pulse oximetry and non‐invasive blood pressure. Sudden damping, followed by disappearance of the capnography curve was recorded during anaesthesia despite the use of intermittent positive pressure ventilation. A tracheal foreign body was found and removed. No macroscopic lesion in the trachea was found. After thoracic drain placement, the cat recovered uneventfully. A rapid, multidisciplinary approach is required when severe tension pneumothorax is present and standard anaesthetic monitoring tools are useful in detecting and solving early complications.